How customer‐oriented companies breed HR flexibility and improved performance: evidence from business‐to‐customer companies in China. (21st June 2019) - Ma, Xifang; Shu, Rui; Zhong, Genyuan
Abstract : The contemporary literature has taken a 'market‐driven' approach to explaining the influence of interaction orientation on organizational performance, but has ignored the internal changes within organizations that are shaped by their customer‐oriented practices. Drawing on the market orientation‐responsiveness‐performance framework (Hult, Ketchen and Slater 2005; Ketchen, Hult and Slater 2007), we provide an alternative explanation for the influence of interaction orientation by articulating the role of a firm's HR flexibility. Using a sample of 156 business‐to‐customer firms located in China, we find that interaction orientation is positively related to organizational performance through its impact on a firm's HR flexibility. Moreover, the association between interaction orientation and HR flexibility is stronger when the organizational culture encourages collective actions (i.e. organizational collectivism). We also discuss the theoretical implications of this research. Key points: Interaction orientation is positively related to organizational performance through its impact on a firm's HR flexibility. The association between interaction orientation and HR flexibility is stronger when the organizational culture encourages collective actions (i.e. organizational collectivism).